(3GdcdGe Ydi bhdg Udi Gddg Ydjg hSde MHH Edi ef OfjGce GdWjH hGdfSGA hLYdJ bQI Yjfi aj GdUdGgs - (3HQgGf GdOjf Hf CHj GdTQjas ((3eMeO Hf UGdM s)
(3ChdgG (B:s
(3hHYO agPg LhGgQ JJMdi HgG CYfGb GdCagGe eSJfHW ef bhdg Ydjg GdUdGI hGdSdGe MHH Edi OfjGce KdGK s
(3BNQgG (B:s
(3hJfbd ai CWhGQ hJcTa Yf CSJGQ cja dG hgj bQI GdYjf Efg bQjH eLjH GdOYhGJ hGdMeO ddg hMOg hUdi Gddg Ydi SjOfG eMeO hBdg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY (B659) s
Keywords: (3GdMOjK h GdeUWdMs